Changes in gender wage differentials in China: a regression and decomposition based on the data of CHIPS1995–2013. Issue 1 (1st January 2019) - Zhao, Xian-Zhou; Zhao, Yu-Bing; Chou, Li-Chen; Leivang, Barbara Hoinunnem
Abstract: Following the enactment of the Labour Law in 1995, China's urban labour market witnessed a divergence in both gender wage gap and discrimination against female workers before 2007, and thereafter a convergence in both. Contributions of endowment differentials between male and female workers to wage gap were diminishing because of the consistent improvement in the female workers' endowments. Discrimination against women, on the other hand, kept increasing and exceeded that of endowment differentials and eventually became the dominating contributor by 2002. Driven by the optimisation of female workers' endowments, the execution of new labour market legislation, the transformation of previously limitless labour supply into shortage, as well as the reform of income distribution policies, a long-term trend of convergence in both gender wage gap and discrimination has been forming. China has been striding forward into a society with more equity and justice ever since 2007.